2006
DOI: 10.1136/tc.2005.015479
|View full text |Cite
|
Sign up to set email alerts
|

Decline in respiratory symptoms in service workers five months after a public smoking ban

Abstract: Objective: To evaluate the effect of a total ban on smoking indoors in restaurants and other hospitality business premises in Norway, on respiratory symptoms among workers in the industry. Methods: Phone interviews with 1525 employees in the hospitality business were conducted immediately before the enacting of the law. In a follow-up study five months later, 906 of the workers from the baseline sample participated. Questions were asked on demographic variables, passive smoking exposure, personal smoking, atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 29 publications
1
39
0
2
Order By: Relevance
“…Reports of passive smoking among the employees decreased from 44% to 6% after the reform. Along with overall increased satisfaction with their new work environment (Hetland, Hetland, Mykletun, Aarø, and Matthiesen, 2008), employees were also less likely to report hoarseness, dry throat, heavy headaches, irritated eyes and tiredness (Eagan, Hetland, and Aarø, 2006). Such positive results were also found in the Scottish and Italian experience with smoking bans (see Gorini 2011 for a review).…”
Section: The 2004 Smoking Ban In Norwaysupporting
confidence: 49%
See 1 more Smart Citation
“…Reports of passive smoking among the employees decreased from 44% to 6% after the reform. Along with overall increased satisfaction with their new work environment (Hetland, Hetland, Mykletun, Aarø, and Matthiesen, 2008), employees were also less likely to report hoarseness, dry throat, heavy headaches, irritated eyes and tiredness (Eagan, Hetland, and Aarø, 2006). Such positive results were also found in the Scottish and Italian experience with smoking bans (see Gorini 2011 for a review).…”
Section: The 2004 Smoking Ban In Norwaysupporting
confidence: 49%
“…While the impact of maternal smoking on the fetus has received considerable attention in the medical literature (Kramer 1987), with its deleterious effects ranging from low birth weight and other birth defects, to childhood and adult asthma and lower cognitive functioning (Horta, Victora, Menezes, Halpern, and Barros 1997;Sayer and Kleinenman 2002;Weitzman, Gortmaker, Walker, and Sobol 1990;Dolan-Mullen, Ramirez, and Groff 1994), the impacts of exposure to second hand smoke is less well studied. On the policy side, while many papers have examined the immediate impacts of taxes or smoking bans on smoking behavior (Brownson, Hopkins, and Wakefield 2002;Eagan, Hetland, and Aarø 2006;Farkas, Gilpin, Distefan, and Pierce 1999;Bitler, Carpenter, and Zavodny 2011;Anger, Kvasnicka, and Siedler 2011), few papers in the economics literature have examined the consequences of such policies on birth outcomes. Evans and Ringel (2001), Lien and Evans (2005) and Simon (2012) are some of the papers that do examine the impact of such policies on smoking during pregnancy and birth outcomes, however, their policy focus is on changes in cigarette taxes rather than smoking bans.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic cough has already been associated with passive smoking [45], and all workers exposed to smoke during their work had higher prevalence of respiratory and irritative symptoms [46]. Additionally, research studying the effects of smoking ban found that the decrease in prevalence of cough and phlegm was significant and relevant in all workers, whether they were smokers or non-smokers [47,48]. Chronic cough was also associated with higher levels of CO that may reflect the inflammation of airways [42], since a study showed that smokers who complained of frequent cough and sputum production had higher levels of ECO compared with smokers without such complaints [43].…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the evidence of increased risk is well-documented, workplaces continue to be the most common sources of ETS exposure among American adults. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In reviews of risk by type of employment, foodservice employees have the highest ETS exposure rates. 5,12 Smoke-free indoor air laws protected only 58% of food-service employees in 1999.…”
mentioning
confidence: 99%